دور النشاط الطلابي في البرنامج الخاص في التحصيل الدراسي للغة العربية بجامعة مولانا مالك إبراهيم مالانق - Uril Bahrudin (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2012)
To be sure, that outdoor student activity in Arabic Intensive Program can’t be dismissed from the educational process, where it’s a part of the curriculum in all educational institutions. Many people were interested of the existing education to put the appropriate status of the student activity. In this case, the researcher wants to discover the role of student activity in Arabic Intensive Program student academic achievement at Maulana Malik Ibrahim State Islamic University Malang, using descriptive approach, and concluded that the Arabic Intensive Program has placed the student activity in special attention equal academic student activity, the student activity in the Arabic Intensive Program has an active role in raising academic achievement for university students.